Visible resonance Raman spectroscopic ex vivo studies of mouse brain and organs - Pei, Zhe; Wu, Binlin; Shi, Lingyan; Zhang, Lin; Boydston-White, Susie; Liu, Cheng-Hui; Alfano, Robert R. (Optical Biopsy XX: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2022)
The unique advantage of visible resonance Raman (VRR) spectroscopy using 532 nm excitation wavelength for biological samples is the resonance enhancement of vibrational modes of chemical bonds from cells and tissues. The aim of this study is specifically to reveal the VRR characteristic spectra of different organs in mice, find the molecular alterations in the development of white matter and gray matter of mouse embryos at different ages and study the VRR spectral information of the mouse embryo head using VRR technology.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy